Explosion hazards study of grid-scale lithium-ion battery energy storage station. (October 2021) - Jin, Yang; Zhao, Zhixing; Miao, Shan; Wang, Qingsong; Sun, Lei; Lu, Hongfei
Highlight: The battery module of 8.8kWh is overcharged in a real energy storage container. The generation and explosion phenomenon of the combustible gases are analyzed. The numerical study on gas explosion of energy storage station are carried out. Abstract: Lithium-ion battery is widely used in the field of energy storage currently. However, the combustible gases produced by the batteries during thermal runaway process may lead to explosions in energy storage station. Here, experimental and numerical studies on the gas explosion hazards of container type lithium-ion battery energy storage station are carried out. In the experiment, the LiFePO4 battery module of 8.8kWh was overcharged to thermal runaway in a real energy storage container, and the combustible gases were ignited to trigger an explosion. The statistics shows that if the combustible gas concentration was not released in time, the combustible gases produced by a single battery module are capable to cause an explosion. Furthermore, a geometric model was established according to the real size energy storage station, and the numerical study of explosion is conducted with vaporized electrolyte selected as the combustible gas. Statistics shows that the overpressure may break through the pressure relief plates on the adjacent containers, and the areas over 343K outside the container are mostly concentrated in the passages parallel to the container doors. Experimental and numerical results above can offer help in upgrading the explosion-proof for energy storage station.